Fasting and postprandial volumes of the undisturbed colon: normal values and changes in diarrhea‐predominant irritable bowel syndrome measured using serial MRI. Issue 1 (17th October 2013) - Pritchard, S. E.; Marciani, L.; Garsed, K. C.; Hoad, C. L.; Thongborisute, W.; Roberts, E.; Gowland, P. A.; Spiller, R. C.
Abstract Background Previous assessments of colon morphology have relied on tests which were either invasive or used ionizing radiation. We aimed to measure regional volumes of the undisturbed colon in healthy volunteers (HV) and patients with diarrhea‐predominant irritable bowel syndrome (IBS‐D). Methods 3D regional (ascending, transverse, and descending) colon volumes were measured in fasting abdominal magnetic resonance (MR) images of 75 HVs and 25 IBS‐D patients. Thirty‐five of the HV and all 25 IBS‐D subjects were fed a standard meal and postprandial MRI data obtained over 225 min. Key Results Colonic regions were identified and 3D maps from cecum to sigmoid flexure were defined. Fasted regional volumes showed wide variation in both HVs being (mean ± SD) ascending colon (AC) 203 ± 75 mL, transverse (TC) 198 ± 79 mL, and descending (DC) 160 ± 86 mL with no difference from IBS‐D subjects (AC 205 ± 69 mL, TC 232 ± 100 mL, and DC 151 ± 71 mL, respectively). The AC volume expanded by 10% after feeding (p = 0.007) in the 35 HV possibly due to increased ileo‐colonic inflow. A later rise in AC volume occurred from t = 90 to t = 240 min as the meal residue entered the cecum. In contrast, IBS‐D subjects showed a much reduced postprandial response of the AC (p < 0.0001) and a greater increase in TC volume after 90 min (p = 0.0244) compared to HV. Conclusions & Inferences We have defined a normal range of the regional volumes of the undisturbed colon in fasted and fed states. The AC in IBS‐D appeared less able to accommodate postprandial inflow which may account for faster colonic transit.